Q: Can this be simplified 6x -9 plus 2x plus 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

It is an expression that can be simplified to: 6x+1

24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)

What are the factors? 2x3 - 8x2 + 6x = 2x(x - 1)(x - 3).

6x^3 + 3x = 3x(2x^2 + 1)

6x + 9 = -3 6x/3 + 9/3 = -3/3 2x + 3 = -1 2x + 3 - 3 = -1 - 3 2x = -4 2x/2 = -4/2 x = -2

Related questions

It is 6x+1 simplified

1* =6

It is an expression that can be simplified to: 6x+1

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2

The value of X in the equation 2x-1-6 5 plus 6x is -3.

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

Fill in the missing powers of x in the dividend by having a coefficient of zero (0); then use long division: _________________ 6x³ - 3x² - 2x + 1 ________--------------------------------- 2x + 1 | 12x⁴ + 0x³ - 7x² + 0x + 1 _________ 12x⁴ + 6x³ _________ ------------- _______________ - 6x³ - 7x² _______________ - 6x³ - 3x² _______________ ------------- ____________________ - 4x² + 0x ____________________ - 4x² - 2x ____________________ ------------ ____________________________ 2x + 1 ____________________________ 2x + 1 ____________________________ -------- __________________________________0 ____________________________ ===== → (12x⁴ - 7x² + 1) ÷ (2x + 1) = 6x³ - 3x² - 2x + 1 with no remainder.

6x + 3 = 2x + 5 4x = 2 x=1/2

In order.6X + 4X = 10X10X - 2X = 8X8X + (1)X = 9X9X-------final answer

6x + 3 = 3(2x + 1)

Assuming there are no parentheses:2 times X - 1 + 4X - 6 + 2X =2X - 1 + 4X - 6 + 2X =2X + 4X + 2X - 1 - 6 =8X - 1 - 6 =8X - 7

6x - 3 = 2x + 1Add 3 to each side:6x = 2x + 4Subtract 2x from each side:4x = 4Divide each side by 4:x = 1